Highly accurate and reliable ultrasonic focusing capability in heterogeneous media using a spherical cavity transducer - Song, Dan; Xiong, Jiupeng; Luo, Man; Gong, Xiaobo; Huang, Wenjun; Zeng, Chen; Zhou, Yufeng; Li, Faqi; Wang, Zhibiao (Frontiers in Physics, 2023)
Focused ultrasound ablation surgery (FUAS) has been emerging to treat a wide range of conditions noninvasively and effectively with promising therapeutic outcomes. The focusing capability of an ultrasound transducer (i.e., focus shift, beam distortion, and acoustic pressure at the focus) determines the ablation effects. However, the focus shift and focal beam distortion after ultrasound propagating through multi-layered heterogeneous viscoelastic biological tissues becomes significant and is found to deteriorate the performance of FUAS in clinics. To achieve an accurate and reliable focal field among patients with large variations in the anatomical structures and properties, a spherical cavity transducer with open ends and sub-wavelength focal size (Li et al., APL, 2013,102:204102) was applied here. Both experimental measurements and numerical simulations were performed to characterize the acoustic fields of the spherical cavity transducer in water, multi-layered concentric cylindrical phantom, and heterogeneous tissue model (adult male pelvis enclosed by porcine skin, fat, and muscle) and then compared with those of a conventional concave transducer at the same electrical power output. It is found that standing-wave focusing using the spherical cavity transducer results in much less focus shift (0.25λ vs. 1.67λ) along the transducer axis and focal beam distortion (-6 dB beam area of 0.71 mm2 vs. 4.72 mm2 in water and 2.55 mm2 vs. 17.30 mm2 in tissue) in the focal plane, but higher pressure focusing gain (40.05 dB vs. 33.61 dB in tissue). Such a highly accurate and reliable focal field is due to the excitation at an appropriate eigen-frequency of the spherical cavity with the varied media inside rather than the reverberation from the concave surface. Together with its sub-wavelength focal size, the spherical cavity transducer is technically advantageous in comparison to the concave one. The improved focusing capability would benefit ultrasound exposure for not only safer and more effective FUAS in clinics but also broad acoustic applications.